Pentecostals in the Public Sphere: Between Counterculturalism and Adaptation (Observations from the Chinese Context in Hong Kong) - Brandner, Tobias (PentecoStudies, 2017)
This paper analyses the public theology of Pentecostalism in the Chinese context of Hong Kong by discussing Pentecostal Christians' public involvement. It asks whether Pentecostal Christians actively shape society or are rather shaped by the surrounding culture and absorb and reflect dominant trends within a culture. The essay explains the different aspects of a Pentecostal public theology in the Chinese context by first giving an overview of different historical forms of Pentecostalism in the Hong Kong and Chinese context, each of them expressing a different pattern of public expression and engagement with public issues. The essay then presents some cases of how Pentecostalism engaged in public issues in Hong Kong. A third part identifies motifs of Pentecostalism that are particularly prominent in the Chinese cultural context. The article suggests that these cultural elements shape the engagement with public spheres and push Pentecostals in the Chinese context towards a public theology that is similar to that of conservative Evangelicals.